MMSE subchannel decision feedback equalization for filter bank based multicarrier systems - Baltar, L.G.; Waldhauser, D.S.; Nossek, J.A. (2009 IEEE International Symposium on Circuits and Systems (ISCAS), 2009)
In this work we present a per-subchannel nonlinear equalizer for a class of filter bank based multicarrier (FBMC) systems. We consider the class of exponentially modulated FBMCs with offset quadrature amplitude modulated (OQAM) input symbols. We design a fractionally spaced decision feedback equalizer (DFE) that minimizes the mean squared error (MMSE) and takes into account the inter-(sub)channel interference (ICI). The input of each equalizer comprises only the output of each subchannel. In the simulation results we show that, despite its increased computational complexity, the performance and the higher bandwidth efficiency of OQAM FBMC systems makes them a competitive alternative to conventional multicarrier systems like cyclic prefix based orthogonal frequency division multiplexing (CP-OFDM).